Use of Caffeine and Inducing Parturition with Dual Administration of Prostaglandin F2α in Gilts and Its Effect on Neonatal Vitality and Performance at Birth - Adrián Alejandro Corrales-Hernández; Herlinda Bonilla-Jaime; Héctor O. Orozco-Gregorio; Ofelia Limón-Morales; Luis Alberto de la Cruz-Cruz; Elías Chávez-Delgadillo; Patricia Roldán-Santiago (Animals)
One of the principal problems in swine production is neonatal mortality, especially in primiparous sows. Caffeine has been shown to be an efficacious neonatal stimulant that reduces mortality while improving key metabolic indicators associated with hypoxic processes. The aim of this study was to evaluate the effect of inducing parturition with a full dose (FD) (175 μg) or split dose (SD) (87.5 + 87.5 μg) of cloprostenol (PGF2α), with and without the administration of a single dose of caffeine (420 mg), on the vitality, clinical status, surface temperature, and weight at weaning of neonate pigs. In this experiment, the duration of farrowing was affected by the induction technique, as the PGF2α SD and PGF2α SD + caffeine treatment groups reduced this time by as much as 100 min compared to PGF2α FD and PGF2α FD + caffeine. The groups that received caffeine presented the best values for the indicators of the neonate performance, peripheral oxygen saturation (SpO2), glucose, surface temperature at 24 h, and weight at 21 days, especially the PGF2α SD + caffeine group. PGF2α FD had the lowest neonate performance and metabolic variables. Inducing birth with PGF2α SD is more efficient, and adding caffeine improves the performance and metabolic variables of piglets born from primiparous sows.